العلاقات الدولية و الايديولوجية مقارية ماركسية - محمود, علي; خمش, حنان (revue mofakir, 2018)
Arab studies which have dealt with the Marxist ideology and its impact on international relations are very limited. Most researchers have not attempted to discuss this subject on a profound level, choosing to tackle it on a shallow one. However, this study attempts to analyze the influence of Marxist ideology on international relations, given that Marxism has played an essential role in political behaviour, economic thinking, social and philosophical ideas. Marxism views the international system as being connected with historical developments, based on socio – economic forces that determine principles and ideals on which human relations are based. Marxist ideology, especially its understanding of the evolution of history and class conflict, has been adopted by many followers and supporters around the world. Although Marxist ideology has played an important role in international relations, yet this role has never been thoroughly examined by analysts, some of whom made a glancing and generic reference to the subject. In order to fulfill its purposes, this study is divided into three sections. The first of which defines international relations according to Arabic and English sources, while the second and third sections discuss the influence of ideology in general, and Marxism in specific, on international relations.